Analysis of historical data of geological layers. - Kayumov Odiljon Abduraufovich (Open Academia, 2024)
This paper explores the analysis of historical geological layer data using advanced stratigraphic techniques and computational tools. It highlights the integration of global stratigraphic databases, biostratigraphy, and seismic modeling to interpret depositional environments, tectonic activity, and climate dynamics. Key findings include the identification of transgressive-regressive cycles linked to eustatic sea-level changes and tectonic subsidence, alongside refined predictive models for resource exploration. The study underscores the transformative potential of machine learning and geoinformatics in enhancing stratigraphic precision. These findings contribute significantly to understanding Earth's geological history, resource management, and environmental reconstruction, providing a framework for future research in stratigraphy and paleoenvironments.
Keywords: Geological stratigraphy; historical data analysis; transgressive-regressive cycles